Mucosal immunotherapy for protection from pneumonic infection with Francisella tularensis - Troyer, Ryan M. (2009)
Previous studies have demonstrated that systemically administered immunotherapy can protect mice from systemic challenge with the bacterial pathogen Francisella tularensis. However, for protection from inhalational challenge with this bacterium, we wondered if mucosally administered immunotherapy might be more effective. Therefore, we administered cationic liposome–DNA complexes (CLDC), which are potent activators of innate immunity, intranasally (i.n.) and assessed the effectiveness of protection from lethal inhalational challenge with F. tularensis. We found that pretreatment by i.n. administration of CLDC 24 h prior to bacterial challenge elicited nearly complete protection of BALB/c mice from lethal challenge with F. tularensis LVS strain. We also observed that mucosal CLDC immunotherapy provided a statistically significant increase in survival time in mice challenged with the highly virulent F. tularensis Schu4 strain. Protection was associated with a significant reduction in bacterial burden in the lungs, liver, and spleen. Mucosal administration of CLDC elicited significantly increased expression of IL-12, IFN-γ, TNF-α, IFN-β and IFN-α genes in the lung as detected by real-time quantitative PCR. In vitro treatment of F. tularensis infected macrophages with CLDC-elicited cytokines also significantly suppressed intracellular replication of F. tularensis in infected macrophages. In vivo, depletion of NK cells prior to administration of CLDC completely abolished the protective effects of CLDC immunotherapy. CLDC-elicited protection was also dependent on induction of IFN-γ production in vivo. We conclude therefore that activation of local pulmonary innate immune responses is capable of eliciting significant protection from inhalational exposure to a virulent bacterial pathogen.